The Prosecution Independence in the Resolution of Inheritance Legal Disputes Involving State Assets or Public Interests - Rasidi, Rasidi; Febrian, Febrian; RS, Iza Rumesten (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The independence of the prosecutor's office is crucial in resolving inheritance law disputes involving state assets or public interest, in order to prevent abuse of authority and potential state losses. Prosecutors often face external pressure when handling strategic inheritance cases that concern public interest. Therefore, this study aims to analyze the extent to which prosecutorial independence is maintained and how its role can be optimized in resolving inheritance disputes with broad impacts. This research is a normative legal study that seeks to identify legal rules, principles, and doctrines through literature review to address the legal issues examined. The research was prescriptive and explanatory in nature, providing systematic and comprehensive explanations and solutions to the legal issues. The approaches used include statutory, conceptual, comparative, and futuristic approaches, with secondary data collected through library research and analyzed qualitatively using a deductive reasoning method. The results show that the independence of the prosecutor's office in resolving inheritance disputes involving state assets or public interest is not yet fully ensured due to external intervention and pressure. The absence of technical guidelines and limited interagency coordination hinder the prosecutor's office from optimally protecting the interests of the state.